Unsteady hydromagnetic Couette flow due to ramped motion of one of the porous plates - Jha, Basant K.; Jibril, Haruna (Zielona Góra: Uniwersytet Zielonogórski)
An unsteady flow formation in Couette motion of an electrically conducting fluid subject to transverse magnetic field has been analyzed in the presence of suction/injection through the porous plates when one of the porous plates is in ramped motion. It is assumed that the porous plates are uniformly permeable and the fluid is entering the flow region through one of the porous plates at same rate as it is leaving through the other porous plate.
Keywords: Couette flow; transverse magnetic field; suction/injection; MHD; ramp motion; Hartmann number; porous plates